Attachment interactions between low-rank coal particles and air/oily bubbles in a microflotation cell. Issue 10 (19th May 2019) - Zhou, You; Albijanic, Boris; Wang, Shiwei; Li, Guosheng; Zhu, Xiangnan
ABSTRACT: The separation of particles by flotation is achieved based on the difference in their surface properties. The controlling step for successful flotation is bubble–particle attachment. The time required for attachment of a particle to an air bubble is defined as the attachment time. Given that attachment times cannot be measured in flotation cells due to the presence of a large number of bubbles and particles which are in motion, the only possibility is to calculate attachment times using the fundamental flotation model. The focus of this paper is to determine the attachment times of low-rank coal in the presence of air bubbles and oily bubbles. The flotation recovery, the rate constant and the attachment efficiency for the oily bubble–coal flotation system were found to be higher than those for the air bubble–coal flotation system. The difference between the flotation rate constants for the air bubble–coal flotation system and that for the oily bubble–coal flotation system was small. However, when considering the difference between the attachment efficiency results, the opposite was true. The relationship between the attachment efficiencies and the attachment times was found to be an exponential decay. The similar trend was also observed for the curve showing the relationship between the flotation rate constants and the attachment times. This work shows the importance of determination of attachment times in coal flotation research.